PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rina Tjandrakirana DP; Meva Monika (Program Studi Magister Manajemen FE Unsri, 2014)
The aim of this research is to examined the influence of money financial to firm value of manufacture companies listed one the Indonesia Stock Exchange. Money financial looks from financial ratios are ROA (Return on Asset) dan ROE (Return on Equity). This research object is manufacture companies listed on Indonesia Stock Exchange since 2009 – 2011. After sample has taken to observated by using method of purposive sampling, there are 74 manufacture companies.The result of this research show that ROA (Return on Asset) and ROE (Return on Equity) have influence to the firm value simultaneously. Partial, only ROE (Return on Equity) has influence to the firm value.